Исследования кургана №2 группы «Бельмак-Могила» вблизи села Трудовое Куйбышевского района Запорожской области / Research on the burial mound no. 2 of the “Bel’mak-Mogila” group near the village of Trudovoe (Kuibyshevo District, Zaporizhia Region) - Valerii Samar; Andrei Antonov (Tyragetia, 2015)
This paper introduces into the scientiﬁc use the results of archaeological investigations undertaken in the burial mound no. 2 near the village of Trudovoe. As a result of the research there were identiﬁed four stages in the process of building of the tumulus. There were also discovered many ﬁndings, such as a bronze cauldron, a granite altar etc., attributed to the Cimmerian culture.